Surface water characteristics in the vicinity of abandoned mercury mine site in Puerto Princesa City, Philippines - Samaniego, Jessie O.; Gibaga, Cris Reven L.; Tanciongco, Alexandria M.; Rastrullo, Rasty M.; Costa, Ma. Azileira V. (2019)
This study was part of an ongoing research project aimed to trace the pathways of possible mercury (Hg) contamination in an abandoned Hg mine site formerly operated by Palawan Quicksilver Mines, Inc. (PQMI) in Puerto Princesa City, Palawan. This mined-out area has been identified as the possible cause for the recent reported Hg poisoning cases among the residents living near the vicinity. To evaluate the water quality in the area, water samples collected from pit lake, river, coast, other nearby streams, leachate from landfill, and hot spring were analyzed for physicochemical parameters and heavy metal concentrations. Results showed that the physicochemical characteristics of freshwater (pit lake and river) and coastal water were generally within the water quality guidelines. Heavy metals in pit lake and river – except for Mn and Ni, Fe, and Mn – were measured within the guidelines, respectively. Hg concentrations in pit lake and river were not detected while low Hg concentrations were measured in coastal water near the jetty (0.001 mg/L) and in hot spring (≤0.0004 mg/L). A landfill near the pit lake was releasing partially-treated leachate with high total suspended solids (TSS) and heavy metal concentrations that contribute to the pollution in the area.
Keywords: Mercury; Mercury contamination